The Effectiveness of Office Space Management of PT. Pegadaian Unit Rappocini Branch in Makassar City - Anggy Noviani Iriansyah; Muh Darwis; Isgunandar Isgunandar (Asha Publishing, 2024)
The physical layout of the office space has a direct impact on improving performance and facilitating productive and successful work outcomes. The purpose of this study is to examine how PT. The Pegadaian Unit of the Rappocini Branch of Makassar City has prepared its office space. The purpose of this qualitative descriptive research project is to evaluate the effectiveness of PT. Office Space Management. Pegadaian Unit Rappocini Branch Makassar City. The informants in this study amounted to seven (seven) people, both direct and visiting clients. Observation, interview, and documentation methods are used in the data collection approach. The data analysis approach of this study uses data presentation, data reduction strategies, findings, and data verification. The findings of this study show the efficacy of PT. Office Space Management. Indicator is part of the Pegadaian Unit of the Rappocini Branch of Makassar City. 1) The principle of shortest distance has been effectively implemented since the office equipment was arranged to meet the needs of employees and facilitate the smooth service process; 2) The order of work of employee placement is based on the ability of the employee; In addition, the employee's sitting position is also adjusted to his workflow to prevent transaction conflicts. so that the transaction process can run quickly and efficiently, 3) The idea of using each space is less than ideal because there are several spaces that have been used and not all of them are divided according to needs. 4) The idea of modifying the workspace layout was successful because the partition material is not permanent so it does not require a lot of time, effort, and cost to modify the layout of the employee's workspace in the future.